First Aid Stick (F.A.S) / Anastasia Vigil Lojonon … [et al.] - Vigil Lojonon, Anastasia; Justinus, Jewel Joy; Abdullah, Mohd Zahiruddin; Henri, Yasmin Atirah; Sun Fatt, Boyd (Faculty of Computer and Mathematical Sciences, 2022)
Outdoor recreational activities have always been favoured by most people around the world and the most preferred activities that people love to do is hiking and trekking. Nowadays, the interest of outdoor recreational activities has been expanded to all ages. However, some hikers and trekkers might have health issues that need immediate medical attention especially for those who have asthma. Moreover, there are also several hikers and trekkers that prefer to bring a stick to avoid falling and getting injured. For that reason, we have come up with an idea which is FIRST AID STICK (F.A.S). Like the first aid box, F.A.S offers the same function. The universal storage tool that is created specifically to assist medical needs or requirement comes in the shape of a hiking and trekking stick that has several storage compartments made of water and moisture resistance, heat resistance, and drop-proof. The stick is antislip and has a mini torchlight along with a mini compass attached at the top. As it is intended for medical use, the compartments are safe to store multiple types of medicine such as inhalers, all-purpose oil, and specific medications prescribed by doctors and pharmacies. The specialty of this product is the ability to fold, and its lightweight material. Overall, this stick is not a normal hiking or trekking stick from the market as it focuses more on medical attention so that it is easier for hikers and trekkers that need medical care to consume or take their medicine right away.